Encefalitis equina venezolana. Perfil clínico epidemiológico de la epidemia ocurrida en 1995 - Colina B José Luis; Blanchard Gabriela (Kasmera, 2003)
Abstract: Equine encephalitis in Venezuela has presented itself in epidemic outbreaks in the Venezuelan Guajira since 1936. In 1938 the causal agent was isolated for the first time in a sick horse in Venezuela. The predominant syndrome is that of a self-limiting illness similar to the common cold, and only 4% of the people infected, principally children under 5 years of age, suffer encephalitis. Mortality in children under 5 with encephalitis is 35%. The clinical epidemiological profile of Equine encephalitis in Venezuela between July 15 and October 17 1995, is described and analyzed in relation to 5 municipalities: Maracaibo, Mara, Padilla, Paez, and Miranda in Zulia State. Data obtained from the epidemiological observance and control departments in Zulia is reviewed, including a total of 11,072 cases of clinical, epidemiological diagnosis of Venezuelan equine encephalitis in a population of 574,769 inhabitants in the five municipalities mentioned. The incidence of contagion is 1.92%, and there is no significant difference between sexes. The age group most affected is children under 5 years old, in which half of the mortality occurred (8 cases). This included 2 newborn children whose mothers contracted the disease in the last three months of pregnancy.